Peran perempuan dalam kepemimpinan di institusi penegak hukum Studi kasus Di Provinsi Daerah Istimewa Yogyakarta - Moh Ramadhan Ilolu; Ishviati J Koenti (Universitas Janabadra, 2020)
The role of women in community development are now beginning to increase, including in the public sector such participations in executive agencies, the legislature and the judiciary. Not only as a government employee, the leadership role of women also started many felt its presence, although not as much as men. This research uses empirical research sociology approach with analytic descriptive study. The data used are primary data and secondary data. The data collection is done with the study of documentation and interviews with the study subjects. Qualitative data were analyzed with descriptive approach and reported in the form of legal writing. The results showed the condition of the apparatus of women and women leaders in the law enforcement agencies in DIY quantitative proportion is still not balanced, still more the male, especially in DIY police agencies. Leadership role of women in the law enforcement agencies in DIY can be viewed from two perspectives, namely general and specific. In general, womens leadership with men it makes no difference, which different is personal character and professionalism.